Comparison of Drug Delivery Systems with Different Types of Nanoparticles in Terms of Cellular Uptake and Responses in Human Endothelial Cells, Pericytes, and Astrocytes - Hakan Sahin; Oguz Yucel; Paul Holloway; Eren Yildirim; Serkan Emik; Gulten Gurdag; Gamze Tanriverdi; Gozde Erkanli Senturk (Pharmaceuticals)
Background/Objectives: The key components of the blood–brain barrier (BBB) are endothelial cells, pericytes, astrocytes, and the capillary basement membrane. The BBB serves as the main barrier for drug delivery to the brain and is the most restrictive endothelial barrier in the body. Nearly all large therapeutic molecules and over 90% of small-molecule drugs cannot cross the BBB. To overcome this challenge, nanotechnology, particularly drug delivery systems such as nanoparticles (NPs), have gained significant attention. Methods: Poly(lactide-co-glycolide) (PLGA) and albumin-based NPs (bovine/human), with or without transferrin (Tf) ligands (BSA, HSA, BSA-Tf, HSA-Tf), and nanolipid carriers (NLC) were synthesized. The interactions of these NPs with human brain microvascular endothelial cells (hBMECs), human brain vascular pericytes (hBVPs), and human astrocytes (hASTROs) were analyzed. Results: At doses of 15.62 µg/mL, 31.25 µg/mL, and 62.5 µg/mL, none of the NPs caused toxic effects on hBMECs, hBVPs, or hASTROs after 3 h of incubation. All NPs were internalized by the cells, but BSA-Tf and HSA-Tf showed significantly higher uptake in hBMECs in a dose-dependent manner. Ultrastructural analysis revealed notable differences between NP formulation and cell type. Conclusions: Our findings underscore the potential of ligand-targeted NPs to selectively interact with BBB endothelial cells. Ultrastructural analysis reveals distinct cellular processing pathways for various NP formulations across BBB-associated cell types, with autophagy emerging as a crucial mechanism for NP handling in pericytes and astrocytes. Changes in NP chemical properties upon biological exposure present significant challenges for nanomedicine design, emphasizing the need for further investigation into NP interactions at the cellular and subcellular levels.